Severity of malnutrition among underweight children and family‐related factors: A cross‐sectional analysis of data from the 2019 Ethiopian Demographic and Health Survey (EDHS) - Gedif M. Alemayehu; Kebadu T. Cherie; Ayele G. Chernet (Health Science Reports, 2022)
Abstract Background and Aims Malnutrition is one of the key factors in children's inappropriate physical and mental development. It is a significant issue that results in the deaths of 3.5 million children under the age of 5 every year worldwide. This study's primary goal was to pinpoint important family‐related causes of underweight child malnutrition in Ethiopia. Methods The data were gathered from the Central Statistical Agency's 2019 Ethiopian Demographic and Health Survey. Data were examined using descriptive statistics and an ordinal logistic regression model after the sample was chosen using a stratified, two‐stage cluster sampling approach. Results Overall 6101 underweight children were involved in the study of which 5019 (82.27%) were severely underweight, 28 (0.46%) were moderately underweight and 1054 (17.28%) were mild. The result showed that, birth order (p < 0.001), partners education, (p < 0.001), partner occupation (p < 0.001) and type of place of residence (p < 0.001) were associated with child malnutrition and also child from poorest family (p = 0.01, adjusted odds ratio [AOR]: 0.745, CI: −0.534, −0.056), children from workless partner (p = 0.169 AOR:CI: 1.855, −0.262, 1.498), and female children (p < 0.001, AOR: 0.793, CI: −0.369,  −0.093) were severely malnourished. Conclusions wealth index combined, sex, and region have statistically significant effect on Severity of malnutrition. Female children were highly malnourished. Children in Amhara, Afar, and Tigray region were highly affected by severe malnutrition relative to other regions. Hence, the government is recommended to impose action on child nutrition in the area as it is a public health issue.